Effect of compression garments on muscle perfusion in delayed-onset muscle soreness: A quantitative analysis using intravoxel incoherent motion MR perfusion imaging - Riexinger, Andreas; Laun, Frederik Bernd; Hoeger, Svenja Alina; Wiesmüller, Marco; Uder, Michael; Hensel, Bernhard; Forst, Raimund; Hotfiel, Thilo; Heiß, Rafael (NMR in Biomedicine, 2021)
The aim of this prospective cohort study was to evaluate the effect of compression garments under resting conditions and after the induction of delayed-onset muscle soreness (DOMS) by MR perfusion imaging using intravoxel incoherent motion (IVIM). Magnetic resonance imaging of both lower legs of 16 volunteers was performed before and after standardized eccentric exercises that induced DOMS. A compression garment (21–22 mmHg) was worn during and for 6 h after exercise on one randomly selected leg. IVIM MR imaging, represented as total muscle perfusion D*f, perfusion fraction f and tissue diffusivity D, were compared between baseline and directly, 30 min, 6 h and 48 h after exhausting exercise with and without compression. Creatine kinase levels and T2-weighted images were acquired at baseline and after 48 h. DOMS was induced in the medial head of the gastrocnemius muscle (MGM) in all volunteers. Compression garments did not show any significant effect on IVIM perfusion parameters at any time point in the MGM or the tibialis anterior muscle (p > 0.05). Microvascular perfusion in the MGM increased significantly in both the compressed and noncompressed leg between baseline measurements and those taken directly after and 30 min after the exercise: the relative median f increased by 31.5% and 24.7% in the compressed and noncompressed leg, respectively, directly after the exercise compared with the baseline value. No significant change in tissue perfusion occurred 48 h after the induction of DOMS compared with baseline. It was concluded that compression garments (21–22 mmHg) do not alter microvascular muscle perfusion at rest, nor do they have any significant effect during the regeneration phase of DOMS. In DOMS, only a short-term effect of increased muscle perfusion (30 min after exercise) was observed, with normalization occurring during regeneration after 6–48 h. The normalization of perfusion independently of compression after 6 h may have implications for diagnostic and therapeutic strategies and for the better understanding of pathophysiological pathways in DOMS.
CRIS-Team Scopus Importer:2021-03-05
Keywords: calf; exercise; intravoxel incoherent motion; magnetic resonance imaging; muscle injury